Placement of re-nests following predation: are birds managing risk?. (1st March 2016) - Beckmann, Christa; McDonald, Paul G.
Abstract: Nest predation is the most important source of reproductive failure for many bird species, thus placing nests in 'safe' locations that minimise predation risk is paramount to maximising fitness. After a nest predation event, some species have been shown to manage the risk of nest predation for subsequent re-nesting attempts by moving to a new location, placing re-nests in areas with increased cover, or changing the height above ground at which the re-nest is placed. The extent to which this is an adaptive behaviour for birds in general is not yet clear, as existing studies are almost exclusively restricted to northern hemisphere species and species that do not breed cooperatively. Here, we examined the re-nesting behaviour of Bell Miners ( Manorina melanophrys ), a species of honeyeater endemic to Australia that is both multi-brooded and also frequently re-nests soon after nesting failure; females can build up to five nests in a breeding season. We tested if these females managed within-season nest predation risk by changing nest site characteristics (height from ground and distance between nests) between successive nesting attempts. We found that female miners did indeed manage predation risk by reducing the height from the ground at which they placed re-nests following predation events, but contrary to our second prediction we found no difference in distances moved to re-nest after females experienced nest predation or successfully rearing young.